Critical Situations and the Flight Safety System - Šumanovac, Darko (Promet - Traffic&Transportation, 2008)
By analyzing and defining events, and then sorting them outinto two distinct groups, this paper will highlight the similarityand frequency of safety factors in a given time frame. The aim isto comprehend the current level of flight safety and compare itto the situation of some fifteen years ago, regardless of technologicalimprovements. This paper shows critical situations asstarting events with possible preventive actions with the aim ofpreventing the development of events with consequences.